OC-010 Large Cohort Study Evaluating the Role of Hybrid ESD (H-ESD) and Conventional Piecemeal EMR Technique in the Resection of Large and Challenging Colonic Polyps Demonstrates no Outcome Benefit of H-ESD over EMR. (4th June 2013) - Bhattacharyya, R; Basford, P; Tholoor, S; Longcroft-Wheaton, G; Bhandari, P
Abstract : Introduction: The learning curve for ESD in the west is very long, so a hybrid technique has been proposed. The impact of Hybrid ESD (H-ESD) technique on clinical outcome is unclear. We aim to compare the outcome benefits of Multi-piece EMR and H-ESD in the resection of challenging colonic polyps. Methods: A Prospective cohort study of endoscopic resection of difficult colonic polyps. Patients were tertiary referrals from experienced endoscopists. EMR was defined as submucosal injection followed by piecemeal snare resection. H-ESD involved submucosal injection before mucosal incision with an ESD knife followed by snare resection of the lesion. Endoscopic follow up was performed. Multiple linear regression analysis was performed using SPSS. Results: 347 flat/sessile polyps > 20 mm were resected between 2007–12. Mean follow-up was 1004 days. H-ESD Cohort: N = 110/347(32%). Mean size was 45mm(range 10–170). 25/110(23%) were salvage procedures for scarred lesions due to failed EMR attempts by other endoscopists. Endoscopic clearance was achieved in 95.5% of procedures. Need for surgery (n = 4): 1 for perforation and 3 for unexpected cancer. 98.6% showed no evidence of recurrence at endoscopic follow up. EMR cohort: N = 237/347(68%). Mean size was 42mm(range 20–150). 11/237(4.6%) were salvage procedures for polyps with scarring. Endoscopic clearance was achieved in 93% of cases. Need for surgery (n = 21): 1 patient for incomplete resection & 20 for suspicion of cancer in EMR specimen. At endoscopic follow up 98% of cases had achieved complete clearance. Risk of recurrence was associated with lesion size > 50 mm & scarring due to previous EMR attempts. This was unaffected by technique (EMR or H-ESD). Perforation/microperforation was more likely in the H-ESD Cohort, but the overall complication rates were similar for H-ESD and EMR cohort. Conclusion: Both techniques achieved an excellent overall cure rate for large & challenging polyps. This is the first large series comparing the two techniques and demonstrates that polyp cure rate was equally good with both techniques. H-ESD technique was used more commonly for polyps with significant scarring & was associated with slightly higher perforation rates. Our data does not demonstrate any significant outcome benefit of H-ESD technique over the conventional EMR technique. Disclosure of Interest: None Declared